Could there be spillover effects between recreational and utilitarian cycling? A multivariate model. (May 2021) - Piras, Francesco; Sottile, Eleonora; Tuveri, Giovanni; Meloni, Italo
Abstract: The current study aims to investigate the impact of socioeconomic and bike infrastructure-related factors on the choice to cycle for different purposes (commuting, errands and leisure/sport) and explores the interplay between these three choices. We developed and estimated a multivariate ordered probit model that accounts for correlation effects among dependent variables, i.e. the three different frequencies of cycling for different purposes, and simultaneously controls for the impact of endogenous and exogenous variables. The data used in this study are drawn from a survey conducted by the University of Cagliari in two mid-size urban areas in Sardinia (Italy). We analysed a sample of 1, 105 individuals with prerequisites useful for the study at hand. Model results show that different socio-demographic variables such as gender, age, level of education, household composition and vehicle ownership influence our dependent variables. The results are consistent with previous research, with males and younger individuals more likely to cycle, while people with children show a lower propensity to use the bike for both transportation and recreational purposes. Further, we show that, in the specific context of the analysis, unobserved effects between the three dependent variables exist and a higher frequency of cycling for leisure leads to a higher frequency of cycling for utilitarian purposes, suggesting the presence of a behavioral spillover effect. Finally, a policy simulation analysis is carried out to estimate the impact of the endogenous variable cycling for leisure on the probability of choosing to cycle for utilitarian purposes. In particular, we find that the adoption of an independent model that ignores the presence of unobserved effects among dependent variables leads to a small overprediction of the number of people cycling for utilitarian purposes.